Pacific Perspective: Canada’s Informal Contribution to the Maritime Defence of the British Empire - Döbler, Tim (The Northern Mariner / Le marin du nord, 2024)
This paper examines Canada’s attitude and informal contributions towards the maritime defence of the British Empire from the mid-nineteenth to the mid-twentieth century. In the late 1850s, the Royal Navy formalized its training of officer cadets and made special arrangements for colonials to become cadets in the senior service. This paper highlights a few British Columbian born and related Royal Navy officers, how they fit in the patterns of imperial mobility of the time, and their contribution to imperial maritime defence. La présente étude traite de la position du Canada et ses contributions informelles à la défense maritime de l’Empire britannique du milieu du 19e siècle au milieu du 20e siècle. À la fin des années 1850, la Marine royale a officialisé la formation des élèves-officiers et a pris des dispositions spéciales pour que les colons deviennent des cadets dans le service. Cette étude met en lumière quelques officiers de la Marine royale originaires de la Colombie-Britannique ainsi que des officiers apparentés, la façon dont ils s’inscrivent dans les modèles de mobilité impériale de l’époque et leur contribution à la défense maritime impériale.